Analisis Skala Usaha dan Ekonomi Budidaya Kolam Ikan Patin di Desa Pihaung Kecamatan Haur Gading Kabupaten Hulu Sungai Utara - Dinasari, Barmawati; Pahlevi, Khairi (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
The purpose of this study is to (1) To find out the scale of the business of cultivating catfish ponds in Pihaung Village, Haur Gading District, Hulu Sungai Utara Regency (2) To find out the benefits or losses on the scale of the business of cultivating catfish ponds in Pihaung Village, Haur Gading District, Hulu Sungai Utara Regency. The scope of this study took the area in Pihaung Village, Haur Gading District, Hulu Sungai Utara Regency. The data source is secondary data and primary data obtained through interviews by filling out a questionnaire sheet that will be done by using the Cobb-Douglas production function method. The result of this study is the scale of catfish pond cultivation business in Pihaung Village, Haur Gading District, Hulu Sungai Utara Regency is at the decreasing return to scale level and has a profit for one year with an average of Rp. 13,363,042.